Practice-based teacher education in physical education - DERVENT, FATİH (My University, 2023)
Background: Teacher education is a complex endeavor designed to prepare preservice teachers for the task of teaching physical education to students in K–12 schools. Yet, there is widespread criticism of teacher education outcomes within the United States and around the world. Consequently, teacher educators have been increasingly called upon to use evidence-based approaches in teacher education. Purpose: In this article, we discuss a teacher education reform called practice-based teacher education from macro and micro perspectives. Discussion: Practice-based teacher education emphasizes a curriculum that is focused on relevance defined in terms of what a teacher needs to know and do to be able to teach physical education. Evidence for curricular changes to physical education teacher education and to the content and pedagogies of methods and content classes are presented. We conclude with a discussion of how practice-based teacher education can address social injustice.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Surgery Medicine Sciences; Orthopedics and Traumatology; Social Sciences and Humanities; Sociology; Education; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; REHABİLİTASYON; ORTOPEDİ; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; REHABILITATION; ORTHOPEDICS; EDUCATION & EDUCATIONAL RESEARCH; Ortopedi ve Spor Hekimliği; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Sosyal Bilimler ve Beşeri Bilimler; Orthopedics and Sports Medicine; Physical Therapy, Sports Therapy and Rehabilitation; Social Sciences & Humanities; core practices; instructional practices; preservice education; social injustice; teacher education pedagogies